Pembelajaran IPA Selama Pandemi Menggunakan Metode Pembelajaran Jarak Jauh (Studi Kasus pada Anak Kelas 4 SD Tunas Muda Jakarta Barat) - Liong Vonny Christianti; Harlinda Syofyan (Journal on Education, 2024)
The Covid19 pandemic is a test for distance learning in Indonesia which has the potential to bring dramatic changes in all areas of life, especially the world of education. This research was conducted with the aim of finding out the obstacles faced by teachers in learning science using distance learning methods and to find out teachers' efforts to optimize science learning using distance learning. This research was carried out at Tunas Muda Elementary School, West Jakarta, with a research duration of one month starting from the second week of December 2022 to the second week of January 2023. The research method applied in this research was descriptive qualitative. The research subjects were the science teachers at Tunas Muda Elementary School in West Jakarta and the research informants in this study were the principal, class teacher and science subject teacher at Tunas Muda Elementary School, West Jakarta. The three data collection techniques in this research include observation, interviews and observations. The application of triangulation techniques is used as a data validity technique in this research. The findings in this research show that the obstacles experienced by teachers as educators are divided into several indicators including 1) the process of delivering learning material 2) interacting with students during the learning process 3) quality of empowering facilities and elements in learning 4) managing teaching materials so that they are easier to understand students 5) prepare the curriculum according to the conditions that occur. Then it has been proven that the teachers or SD Tunas Muda West Jakarta have made various efforts and adjustments aimed at optimizing science learning which is carried out using distance learning methods.